Comparison of amino acid metabolism in frozen‐thawed and fresh early‐stage human embryos. Issue 6 (3rd April 2013) - Fang, Cong; Tang, Jie; Huang, Rui; Li, Li‐lin; Zhang, Min‐fang; Liang, Xiao‐yang
Abstract Aims To compare the amino acid differences of changes of frozen‐thawed early‐stage human embryos and fresh cultured early‐stage human embryos. Material and Methods Discarded embryos and their in vitro culture medium of patients who underwent in vitro fertilization‐embryo transfer (IVF‐ET) at the Research Center for Reproductive Medicine, the Sixth Affiliated Hospital of Sun Yat‐sen University, from September 2010 to April 2011 were collected. Amino acid levels were determined by high performance liquid chromatography. Results The amino acid differences of changes in the culture medium of fresh embryos (661.50 μmol/L) were significantly higher than in the medium of post‐thawed embryos (232.00 μmol/L) at 0.5 h (P < 0.001). At 1 and 2 h, no significant difference of change was found in all amino acids. Differences in the concentration of amino acids between post‐thawed embryos and blank control medium were already present beginning at 1 h. Conclusions The level of amino acid metabolism of frozen‐thawed early‐stage human embryos has already recovered from the state of metabolic stagnation during cryopreservation at 1 h of incubation after thawing, and the amino acid metabolism level at that time approximates that in fresh embryos before freezing. This may be established as the optimal embryo transfer time in IVF‐ET.